The first knowledge economy : human capital and the European economy, 1750-1850 - Jacob, Margaret C., 1943- (Cambridge : Cambridge university press, 2014)
"Ever since the Industrial Revolution debate has raged about the sources of the new, sustained western prosperity. Margaret Jacob here argues persuasively for the critical importance of knowledge in breaking the Malthusian trap during the period from 1750 to 1850, first in Britain and then in selected parts of northern and western Europe. This is a new history of economic development in which minds, books, lectures and education become central. She shows how, armed with knowledge and know-how and inspired by the desire to get rich, entrepreneurs emerged within an industrial culture wedded to scientific knowledge and technology. She charts how, across a series of industries and nations, innovative engineers and entrepreneurs sought to make sense and a profit out of the world around them. Skilled hands matched minds steeped in the knowledge systems new to the eighteenth century to transform the economic destiny of western Europe"--
"Knowledge and Industrial Development: The Stakes By "the first knowledge economy" we refer to the era of the Industrial Revolution, from roughly the 1760s to the 1850s, first in Britain and then in selected parts of northern and western Europe, with particular attention to Belgium"--
Introduction: knowledge and industrial development: the stakes -- 1. A portrait of early industrial lives: the Watts and Boultons, science and entrepreneurship -- 2. The knowledge economy and coal: how technological change happened -- 3. Technical knowledge and making cotton king -- 4. Textiles in Leeds: Mechanical science on the factory floor -- 5. The puzzle of French retardation I: reform and its antecedents -- 6. The puzzle of French retardation II: restoration and reaction -- 7. Education and the inculcation of industrial knowledge: the Low Countries, 1750-1830.
Bibliografische referenties ; index
Keywords: Bauwens, Livinus Jan, -- 1769-1822.; Economic development -- History -- Europe; HISTORY / Europe / General; Industrialization -- History -- Europe; Technological innovations -- Economic aspects -- History -- Europe